Method for producing conductive film, dispersion liquid, radiation-sensitive resin composition, and light-emitting element

By coating the dispersion of functional-based polymer and CNT on the substrate, and forming a conductive film using a radiation-sensitive resin composition, the problem of easy coagulation and disconnection of the CNT conductive film in the drying process is solved, and the effect of high conductivity and uniform fixation is achieved.

CN119816381APending Publication Date: 2025-04-11JSR CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062324.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-02
Filing Date
2023-08-15
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the conductive film formed of CNT is prone to coagulation in the drying process, resulting in damage to homogeneity, and is difficult to be formed stably, making it easy to cause disconnection.

Method used

A manufacturing method is adopted, including coating a dispersion of a first polymer containing a functional group and a carbon material on the main surface of the substrate, and drying it to form a first film; then coating a radiation-sensitive linear resin composition containing a second polymer containing a functional group and a photoacid generator on the first film, forming a second film, and exposing a portion thereof to remove the polymer of the unexposed portion.

Benefits of technology

High conductivity and uniform fixation of the conductive film are achieved, and the polymer in the unexposed portion of the dispersant and radiation-sensitive linear resin composition is effectively removed, thereby avoiding the problem of disconnection of the conductive film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816381A_ABST
    Figure CN119816381A_ABST
Patent Text Reader

Abstract

Provided is a method for producing a conductive film which has high conductivity and which is capable of uniformly fixing a conductive carbon material over the entire conductive film formation region. Also provided is a production method capable of efficiently removing a dispersant remaining in the conductive film and a polymer in an unexposed portion of the radiation-sensitive resin composition. The present invention comprises: a step (A) in which a dispersion containing a carbon material and a first polymer having any one functional group selected from among a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group is applied to the main surface of a substrate and dried to form a first film; a step (B) in which a radiation-sensitive resin composition containing an acid generator and a second polymer having any one functional group selected from the group consisting of a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group is applied to the first film to form a second film; a step (C) for exposing the second film to light; and a step (D) in which, after the step (C), the first polymer and the second polymer are removed by development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a conductive film, a dispersion liquid used in the method for producing a conductive film, a radiation-sensitive resin composition, and a light-emitting element produced using the method for producing a conductive film. Background Art

[0002] In recent years, a semiconductor device having an electrode or wiring formed by a conductive film of a nanocarbon material is being developed. In the past, the electrodes or wiring of semiconductor devices were mostly formed by metals such as copper or aluminum. However, compared with metals or metal oxide films, nanocarbon materials, particularly carbon nanotubes (carbon nanotube, CNT) (hereinafter sometimes referred to as "CNT") can be made very thin and show high conductivity, and therefore receive high attention as materials for semiconductor devices. In addition, the conductive film formed by the nanocarbon material can form a film that shows high transmittance to visible light, and therefore there is a trend of being actively used in semiconductor optical elements.

[0003] Against such background, various proposals have been made regarding materials and production methods, particularly for conductive films formed of CNTs. For example, Patent Document 1 below discloses a composition containing a solvent and CNTs as a composition having improved dispersibility of CNTs.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-214837 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the conductive film produced by the composition has the following problems: aggregation is easily generated during the drying process, and the homogeneity is easily impaired. Regarding the CNT transparent conductive film, since the fibrous CNTs overlap like non-woven fabrics to form a circuit in which current flows, it exhibits conductivity. Therefore, unlike metal films or metal oxide films, it is difficult to form a stable characteristic and it is difficult to exhibit stable electrical properties.

[0009] In particular, in semiconductor devices such as large-scale integrated circuits (LSI) that are being miniaturized, the wiring width is very narrow. Therefore, if wiring is formed from a conductive film of CNT, there is a problem that the wiring has locally high resistance or is prone to disconnection.

[0010] In addition, when used in a light-emitting element or a touch screen, in order to improve the transmittance to visible light, it is required to form a conductive film as thin as possible, and it is required to form a conductive film with high conductivity and homogeneity. In this case, as with the semiconductor devices such as LSI described above, there is also a problem that the conductive film is prone to disconnection. More specifically, for example, when the wiring constituting the touch screen is composed of wiring with a width of less than 50 μm, or when the pixel electrode of the display panel is made, a lead wire is made from a contact hole with a width of less than 50 μm, it is particularly easy to break the wire. Furthermore, when a radiation-sensitive resin composition is applied to such a conductive film and a pattern of an insulating layer is formed, sometimes a part of the CNT conductive film peels off. In addition, there are potential problems such as adding a new process to prevent the peeling of the CNT conductive film.

[0011] In view of the above problems, the present invention aims to provide a method for producing a conductive film having high conductivity and capable of uniformly fixing a conductive carbon material throughout the entire conductive film forming region. In addition, the present invention aims to provide a method for producing a conductive film capable of efficiently removing a dispersant remaining in the conductive film and a polymer in a portion of a radiation-sensitive resin composition that is not exposed.

[0012] Technical means of solving problems

[0013] The method for manufacturing a conductive film of the present invention comprises:

[0014] Step (A), coating a dispersion of a first polymer having any one of a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group and a carbon material on a main surface of a substrate and drying the dispersion to form a first film;

[0015] Step (B), coating the first film with a radiation-sensitive resin composition containing a second polymer having any one of a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group and a photoacid generator to form a second film;

[0016] Step (C), exposing a portion of the second film to light; and

[0017] A step (D) of removing the first polymer and the second polymer in the portion exposed in the step (C) after the step (C) is performed.

[0018] In addition, the manufacturing method may also include:

[0019] Step (E) is to heat-treat the substrate after performing the step (D).

[0020] The manufacturing method may also be as follows:

[0021] The step (A) applies the first polymer having a polyamic acid structure, and the step (B) applies the second polymer having a polyamic acid structure.

[0022] The manufacturing method may also be as follows:

[0023] The step (A) is to apply the dispersion containing the first polymer having a polyamic acid structure and an organic solvent.

[0024] The "polyamic acid structure" mentioned here is a structure having a partial structure including a carboxyl group, and the partial structure is dehydrated and ring-closed by heating to form an imide structure.

[0025] The manufacturing method may also be as follows:

[0026] The step (B) is to apply the radiation-sensitive resin composition containing the second polymer having a polyamic acid having a structural unit represented by the following general formula (1) as a main component.

[0027] [Chemistry 1]

[0028]

[0029] (In formula (1), R 1 is a tetravalent organic group constituting a tetracarboxylic acid, R 2 is a divalent organic group constituting a diamine, and n represents a positive integer)

[0030] In this specification, the term "main component" refers to a substance having the highest content rate among substances contained in a material.

[0031] The manufacturing method may also be as follows:

[0032] The step (A) comprises applying the dispersion containing at least one carbon material selected from the group consisting of carbon nanotubes, graphene, and fullerene.

[0033] The manufacturing method may also be as follows:

[0034] The step (B) is to apply the radiation-sensitive resin composition containing a quinonediazide compound as the photoacid generator.

[0035] The manufacturing method may also be as follows:

[0036] The step (B) is to apply the radiation-sensitive resin composition containing a colorant.

[0037] The manufacturing method may also be as follows:

[0038] The step (A) includes applying the dispersion liquid containing the first polymer in an amount ranging from 1,000% by mass to 10,0000% by mass based on the content of the carbon material.

[0039] The manufacturing method may also be as follows:

[0040] In the step (A), the dispersion is applied by any coating method selected from the group consisting of spin coating, slit coating, bar coating, spray coating, and ink-jet.

[0041] The manufacturing method may also be as follows:

[0042] In the step (B), the radiation sensitive resin composition is applied by any coating method selected from the group consisting of spin coating, slit coating, bar coating, spray coating, and ink jet coating.

[0043] The manufacturing method may also be as follows:

[0044] In the step (C), exposure is performed through a half tone mask.

[0045] The manufacturing method may also be as follows:

[0046] In the step (D), an alkaline aqueous solution, an organic solvent, or a mixed solution thereof is used as a developer to remove the first polymer and the second polymer.

[0047] The production method may include step (E), step (F) and step (G):

[0048] The step (E) is to remove the exposed carbon material by etching after performing the step (D);

[0049] The step (F) is further to expose a portion of the second film after the step (E) is performed;

[0050] The step (G) removes the first polymer and the second polymer in the portion exposed in the step (F).

[0051] The dispersion of the present invention is

[0052] The dispersion used in the production method.

[0053] The radiation sensitive resin composition of the present invention is

[0054] A radiation-sensitive resin composition used in the production method.

[0055] The light emitting element of the present invention is

[0056] A light-emitting element including a conductive film manufactured by the manufacturing method.

[0057] Effects of the Invention

[0058] The present invention can realize a method for producing a conductive film having high conductivity and in which a conductive carbon material can be uniformly fixed over the entire conductive film forming region. In addition, the present invention can realize a method for producing a conductive film capable of efficiently removing a dispersant remaining in the conductive film and a polymer in a portion of a radiation-sensitive resin composition that is not exposed. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] [ Figure 1 ] is a schematic diagram showing the overall structure of one embodiment of a display panel.

[0060] [ Figure 2 ] is a diagram schematically showing the process of forming a conductive film.

[0061] [ Figure 3 ] is a diagram schematically showing the process of forming a conductive film.

[0062] [ Figure 4 ] is a diagram schematically showing the process of forming a conductive film.

[0063] [ Figure 5 ] is a diagram schematically showing the process of forming a conductive film.

[0064] [ Figure 6 ] is a diagram schematically showing the process of forming a conductive film.

[0065] [ Figure 7 ] is a photograph of the surface of the substrate taken using AFM.

[0066] [ Figure 8 ] is a photograph of the surface of the substrate taken using AFM. DETAILED DESCRIPTION

[0067] Hereinafter, the structure of the display panel 1 as one embodiment is first described, and then one embodiment of the method for manufacturing the conductive film included in the display panel 1 is described in detail. In addition, a verification evaluation experiment for confirming the dispersibility or coating property of the dispersion liquid or the radiation-sensitive resin composition is performed through one example related to the method for manufacturing the conductive film, and therefore, the verification evaluation experiment is finally described in detail.

[0068] [Display Panel]

[0069] The overall structure of one embodiment of the display panel 1 will be described. Figure 1 1 is a schematic diagram showing the overall structure of one embodiment of a display panel 1. The display panel 1 includes a substrate 2, and a device region 2a and a peripheral region 2b are provided on one surface of the substrate 2.

[0070] The substrate 2 is formed of a light-transmitting material, and specifically, for example, a glass substrate, a quartz substrate, or an organic resin substrate. As a material of the organic resin substrate, for example, polyimide can be cited. The organic resin substrate can have a thickness of several microns to tens of microns, thereby realizing a flexible sheet display.

[0071] The device region 2a is a region where devices for displaying images are formed. A lower electrode is provided in the device region 2a, an insulating layer is provided on the lower electrode, an organic resin layer is provided on the insulating layer, and a conductive film is provided on the organic resin layer.

[0072] The material of the organic resin layer is an organic material containing a polymer having a hydrocarbon group. The material of the conductive film is CNT. As the type of CNT, single-walled carbon nanotubes or multi-walled carbon nanotubes with two or more layers can be used, preferably single-walled carbon nanotubes.

[0073] The transmittance of a conductive film made of carbon nanotubes varies depending on the film thickness, but it becomes a transparent conductive film that transmits visible light.

[0074] The material constituting the organic resin layer is an organic resin material containing a polymer having a hydrocarbon group. Examples of the material constituting the organic resin layer include polyimide resins, polyamide resins, polyether resins, polyester resins, etc., but are not particularly limited. In addition, from the perspective of the adhesion of carbon nanotubes, the material constituting the organic resin layer is preferably a material containing aromatic hydrocarbons, and more preferably a material containing polycyclic aromatic hydrocarbons.

[0075] The coating film, i.e., the first film, used to form the conductive film of the present embodiment can be formed by coating a dispersion liquid containing carbon nanotubes and a first polymer as a dispersant. The first polymer is not particularly limited, but in terms of improving the dispersibility of the carbon nanotubes, it is preferred to use a polymer having a polyamic acid having a structural unit represented by formula (1) as a main component. Formula (1) is described again for the sake of caution.

[0076] [Chemistry 2]

[0077]

[0078] (In formula (1), R 1 is a tetravalent organic group constituting a tetracarboxylic acid, R2 is a divalent organic group constituting a diamine, and n represents a positive integer)

[0079] As R 1 Specific examples of the tetravalent organic group constituting the tetracarboxylic acid represented by the tetravalent organic group include pyromellitic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 2,3,6,7-anthracenetetracarboxylic acid, 1,2,5,6-anthracenetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4-biphenyltetracarboxylic acid, bis(3,4-dicarboxyphenyl)ether, 3,3'4,4'-benzophenonetetracarboxylic acid, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)methane, 2,2-bis(3,4-dicarboxyphenyl)propane, 1,1,1,3,3,3-hexafluoro- Dianhydrides of aromatic tetracarboxylic acids such as 2,2-bis(3,4-dicarboxyphenyl)propane, bis(3,4-dicarboxyphenyl)dimethylsilane, bis(3,4-dicarboxyphenyl)diphenylsilane, 2,3,4,5-pyridinetetracarboxylic acid, and 2,6-bis(3,4-dicarboxyphenyl)pyridine; Dianhydrides of tetracarboxylic acids having an alicyclic structure such as 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, 2,3,5-tricarboxycyclopentylacetic acid, and 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic acid; Dianhydrides of aliphatic tetracarboxylic acids such as 1,2,3,4-butanetetracarboxylic acid, etc. These acid dianhydrides may be used alone or in combination of a plurality of compounds.

[0080] As R 2Specific examples of the divalent organic group constituting the diamine represented by the formula include p-phenylenediamine, m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, diaminodiphenylmethane, diaminodiphenyl ether, 2,2'-diaminodiphenylpropane, bis(3,5-diethyl-4-aminophenyl)methane, diaminodiphenyl sulfone, diaminobenzophenone, diaminonaphthalene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenyl)benzene, 9,10-bis(4-aminophenyl)anthracene, 1,3-bis(4-aminophenyl)anthracene, Aromatic diamines such as bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane; alicyclic diamines such as bis(4-aminocyclohexyl)methane, bis(4-amino-3-methylcyclohexyl)methane, 3,5-diaminobenzoic acid cholesteryl ester; and aliphatic diamines such as 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,6-diaminohexane; and silicon diamines such as 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane. These diamines may be used alone or in combination of a plurality of compounds.

[0081] Furthermore, R of the formula (1) 1 The cyclobutane ring is preferably used because the ring structure of the cyclobutane ring is decomposed by light irradiation or heating, causing a change in the structure of the polyamic acid, thereby making it easy to remove the polyamic acid as the first polymer. In addition, the dispersion may contain, for example, an organic solvent as a dispersion medium.

[0082] The radiation-sensitive resin composition for coating on the first film and forming an insulating layer pattern comprises a polyamic acid (second polymer) having a structural part represented by the formula (1) contained in the coating solution for forming the first film. The polyamic acid shows solubility in an alkaline aqueous solution, so it can be removed by using an alkaline aqueous solution, for example. That is, the alkaline aqueous solution can be used as a developer.

[0083] In addition, as a developer, an alkaline aqueous solution, an organic solvent, or any of these mixed solutions is preferred, but as long as the material can remove the first polymer, solutions other than these can also be used. As another example of a combination of a polymer and a developer, a combination such as a polymer having a carboxyl group and a tetramethylammonium hydroxide (TMAH) aqueous solution can be used.

[0084] The radiation-sensitive resin composition is a material applied on a first film to form a second film, and a pattern is formed on a conductive film by exposing and developing a portion of the second film. The first polymer remaining in the first film during the development and the first polymer and the second polymer in the exposed portion of the radiation-sensitive resin composition can be removed simultaneously by a single development.

[0085] The polymer of the unexposed part is heated to dehydrate a part of the polyamic acid structure and become a polyimide structure. Polyimide is used to form an insulating layer due to its high insulation and excellent resistance to organic solvents. In the case of display panels such as organic electroluminescence (EL), such polyimide can be used for the bank layer formed when dividing the light-emitting area.

[0086] The radiation-sensitive resin composition comprises a polyamic acid represented by formula (1), and as long as it has a polyamic acid structure, a part of the substituents may be different. Furthermore, it may also contain an alkali-soluble resin other than polyamic acid. As such an alkali-soluble resin, there can be cited polymers obtained by using an unsaturated compound containing a carboxyl group as an alkali-soluble group as a monomer and performing free radical polymerization, and as other alkali-soluble resins, there can be used: silane, a resin containing a cardo skeleton, a phenol novolac resin, a cresol novolac resin, a biphenyl resin, a bisphenol A type resin, a bisphenol F type resin, a resin having a dicyclopentane skeleton, a resin having a trisphenol methane skeleton, a bisphenol F type epoxy resin, a multifunctional epoxy resin, a flexible epoxy resin, a brominated ring Epoxy resins, glycidyl ester epoxy resins, phenoxy resins, biphenyl epoxy resins, silicone resins, polyhydroxystyrene resins, styrene-hydroxystyrene copolymer resins; bisphenol A series, bisphenol F series, bisphenol AD ​​series, bromine-containing bisphenol A series, phenol novolac series, cresol novolac series, polyphenol series, linear aliphatic series, butadiene series, carbamate series and other glycidyl ether epoxy resins; hexahydrophthalic acid glycidyl ester, dimer acid glycidyl ester, aromatic series, cyclic aliphatic series, aliphatic glycidyl ester epoxy resins, etc.

[0087] The radiation-sensitive resin composition contains a photoacid generator and functions as a positive radiation-sensitive material. As the photoacid generator, a quinonediazide compound is particularly preferred. The quinonediazide compound generates carboxylic acid by irradiation with radiation. By containing the quinonediazide compound, a positive radiation-sensitive property of removing the exposed part by the development process can be imparted to the positive radiation-sensitive resin composition.

[0088] As the quinonediazide compound, preferably, there can be mentioned a condensate of a compound having a phenolic hydroxyl group and a naphthoquinonediazidesulfonyl halide. As the compound having a phenolic hydroxyl group, for example, there can be mentioned the following compounds.

[0089] [Chemistry 3]

[0090]

[0091] [Chemistry 4]

[0092]

[0093] Among these, as the compound having a phenolic hydroxyl group, 4,4′-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylene]bisphenol and 1,1,1-tri(p-hydroxyphenyl)ethane are preferred.

[0094] Examples of the naphthoquinonediazidesulfonyl halide include 1,2-naphthoquinonediazide-4-sulfonyl chloride and 1,2-naphthoquinonediazide-5-sulfonyl chloride. The ester compound (quinonediazide compound) obtained from 1,2-naphthoquinonediazide-4-sulfonyl chloride has absorption in the i-ray (wavelength 365 nm) region and is therefore suitable for i-ray exposure. On the other hand, the ester compound (quinonediazide compound) obtained from 1,2-naphthoquinonediazide-5-sulfonyl chloride has absorption in a wide range of wavelength regions and is therefore suitable for exposure at a wide range of wavelengths.

[0095] The quinonediazide compound is preferably a condensate of 4,4′-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylene]bisphenol and 1,2-naphthoquinonediazide-5-sulfonyl chloride, or a condensate of 1,1,1-tri(p-hydroxyphenyl)ethane and 1,2-naphthoquinonediazide-5-sulfonyl chloride.

[0096] The quinone diazide compound can be used alone or in combination of two or more. The content of the quinone diazide compound in the radiation-sensitive resin composition is preferably 1 to 100 parts by mass, and more preferably 5 to 50 parts by mass, relative to 100 parts by mass of polyamic acid. By setting the content of the quinone diazide compound to the specific range, the difference in solubility between the irradiated part and the unirradiated part of the radiation in the alkaline aqueous solution that becomes the developer becomes larger, and as a result, the patterning performance becomes better. In addition, the solvent resistance of the obtained insulating film also becomes better.

[0097] In the case of forming an organic EL bank, the photosensitive resin composition may include a colorant for imparting reflectivity or light-shielding properties to the bank. Specifically, the colorant includes at least one colorant selected from the group consisting of a white pigment, a black organic colorant, a black inorganic colorant, and a colorant other than black. The colorant is a mixture of two or more inorganic colorants or organic colorants.

[0098] When the bank of the organic EL is given reflectivity, a white pigment can be used. As the white pigment, for example, it can be selected from aluminum oxide, magnesium oxide, antimony oxide, titanium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, barium sulfate, magnesium carbonate, barium carbonate, calcium carbonate, lead sulfate, lead phosphate, zinc phosphate, silicon dioxide, zinc oxide, tin oxide, strontium sulfide, strontium titanate, barium tungstate, lead metasilicate, talc, kaolin, clay, bismuth oxychloride, hollow silica particles, organic hollow particles, core-shell particles, etc.

[0099] The white pigment preferably contains at least one inorganic substance selected from the group consisting of aluminum oxide, magnesium oxide, antimony oxide, titanium oxide, zirconium oxide, aluminum hydroxide, magnesium hydroxide, barium sulfate, magnesium carbonate, and barium carbonate, and particularly preferably contains titanium oxide. The inorganic substance has a high refractive index and can improve the reflection characteristics of the formed cured film. Among them, titanium oxide has a particularly high refractive index and is also preferred from the viewpoint of dispersion characteristics in a solvent.

[0100] The lower limit of the mean particle diameter of white pigment is preferably 50nm, is preferably 100nm, and is more preferably 200nm. On the other hand, its upper limit is preferably 700nm, is more preferably 500nm, and then is preferably 400nm. The mean particle diameter by white pigment is described in the scope, can play good dispersibility and light scattering etc., as a result, can improve light reflectivity and light-shielding property.

[0101] In the case of imparting light-shielding properties to the bank of the organic EL, at least one colorant selected from the group consisting of a black organic colorant, a black inorganic colorant, and a colorant other than black can be used. Specifically, any black inorganic colorant, any black organic colorant, and any colorant other than black that are currently available in the art can be used. For example, any compound classified as a pigment in the Color Index (a journal of the Association of Dyeing and Color Technicians) and dyes currently available in the art can be used. A specific example of a black organic colorant is at least one selected from the group consisting of aniline black, lactam black, and perylene black.

[0102] Among these, lactam black represented by the following formula (for example, Irgaphor Black S 0100CF manufactured by BASF) is preferably used in terms of optical density, dielectric constant, transmittance, and the like.

[0103] [Chemistry 5]

[0104]

[0105] In addition, as perylene black, perylene black represented by the following formula (Lumogen Black FK42809 manufactured by BASF) is preferably used in terms of optical density, dielectric constant, transmittance, and the like.

[0106] [Chemistry 6]

[0107]

[0108] Specific examples of the black inorganic colorant include carbon black, titanium black, metal oxides such as Cu-Fe-Mn oxides, synthetic iron black, etc. Among them, carbon black is preferably used from the viewpoint of pattern characteristics and chemical resistance.

[0109] Specific examples of colorants other than black include CI Pigment Violet 13, 14, 19, 23, 25, 27, 29, 32, 33, 36, 37, and 38 and CI Pigment Blue 15 (15:3, 15:4, 15:6, etc.), 16, 21, 28, 60, 64, and 76. Specifically, the colorant other than black may include at least one colorant selected from the group consisting of a blue colorant and a magenta colorant. Among them, CI Pigment Blue 15:6 and 60 or CI Pigment Violet 23 is preferred from the viewpoint of reducing reflectivity.

[0110] The photosensitive resin composition contains 1% to 50% by mass, preferably 5% to 20% by mass, of a colorant relative to the total amount of the photosensitive resin composition. If 1% to 50% by mass of the colorant is contained, the optical density is excellent, and if 5% to 20% by mass is contained, the optical density can be further excellent. In addition, the solid content in the photosensitive resin composition refers to the total of the components after removing the solvent.

[0111] The radiation-sensitive resin composition may also contain other optional components such as a photoacid generator (other than a quinonediazide compound), an antioxidant, a multifunctional acrylate, a surfactant, a close contact aid, inorganic oxide particles, a compound having a cyclic ether group, and a solvent. Other optional components may be used alone or in combination of two or more.

[0112] [Manufacturing method]

[0113] Reference Figure 2 to Figure 6 A method for producing the conductive film will be described. Figure 2 to Figure 6 2 is a diagram schematically showing a process of forming a conductive film. In addition, the method for producing a conductive film according to the present embodiment is to produce a conductive film on an organic resin layer formed on a substrate.

[0114] like Figure 2As shown, an organic resin material including a polymer having a hydrocarbon group is applied on the substrate 2 having the insulating layer 10 formed thereon, thereby forming the organic resin layer 20 .

[0115] First, if Figure 2 As shown, a dispersion liquid containing polyamic acid 30a, CNT 30c, and an organic solvent as a dispersion medium is applied on a substrate having an organic resin layer 20 formed thereon to form a pattern of a coating film 30 (step S1).

[0116] Then, the coating film 30 is dried to volatilize the organic solvent, thereby Figure 3 As shown, the polyamic acid 30a and the CNT 30c are fixed on the organic resin layer 20 to form the first film 40 (step S2). Steps S1 and S2 correspond to step (A).

[0117] In step S1 , a pattern formed of a coating film of a dispersion liquid containing CNTs is formed on the organic resin layer 20 using a printing technique such as casting, screen printing, or inkjet.

[0118] After forming the first film 40 on the organic resin layer 20, Figure 4 As shown, a radiation sensitive resin composition is applied on the organic resin layer 20 on which the first film 40 is formed, thereby forming the second film 50 (step S3). The step S3 corresponds to step (B).

[0119] After forming the second film 50, as Figure 5 As shown, the exposure portion A1 of the second film 50 is exposed through the photomask 60 (step S4). The step S4 corresponds to step (C).

[0120] The radiation-sensitive resin composition forming the second film 50 contains a quinonediazide compound and thus functions as a positive-type radiation-sensitive resin material. The exposure portion A1 is dissolved in the alkaline aqueous solution by converting the quinonediazide compound into an indenecarboxylic acid structure.

[0121] When performing exposure, exposure is usually performed through a photomask having a predetermined pattern. The radiation L1 used in the exposure is preferably radiation having a wavelength in the range of 190 nm to 450 nm, and more preferably radiation containing ultraviolet rays of 365 nm. The exposure dose is preferably 500 J / m 2 ~6,000J / m 2 , more preferably 1,500 J / m 2 ~1,800J / m 2The exposure amount refers to the value obtained by measuring the intensity of the radiation at a wavelength of 365 nm using an illuminometer ("OAI model 356" from OAI Optical Associates). A halftone mask can be used as the photomask 60. By using a halftone mask, the shape of the resulting pattern can be controlled. Specifically, the inclination (also called the tapered shape) of the side wall of the pattern can be controlled.

[0122] After step S4, Figure 6 As shown, after the exposure, the polyamide acid 30a, which is the second polymer of the radiation-sensitive resin composition layer in the exposed portion A1, is removed by development using an alkaline aqueous solution as a developer (step S5). The step S5 corresponds to step (D).

[0123] Through the above steps S1 to S5, a region is formed on the organic resin layer 20 in which the conductive film 70 is formed in a part and the second film 50 remains in the other part. Figure 6 As shown, the conductive film 70 has a structure in which the CNTs 30 c are dispersed, and is transmissive to visible light, that is, transparent.

[0124] The first polymer in the dispersion and the second polymer contained in the radiation-sensitive resin composition are polymers having a polyamic acid structure. The polymer having a polyamic acid structure has a carboxyl group in the molecule and therefore exhibits high solubility in an alkaline aqueous developer.

[0125] By developing with an alkaline aqueous developer, the polyamic acid 30a of the first film 40 and the polyamic acid 30a of the second film 50 in the exposure portion A1 can be removed simultaneously. Furthermore, by heating and drying after development, the conductive film 70 with the polyamic acid removed and the pattern in which the polyamic acid is changed to a polyimide structure can be formed.

[0126] As the alkaline aqueous solution, for example, a potassium hydroxide (KOH) aqueous solution, a sodium hydroxide (NaOH) aqueous solution, a sodium carbonate aqueous solution, a tetramethylammonium hydroxide (TMAH) aqueous solution, or the like can be preferably used.

[0127] After step S5, the polyamic acid 30a of the first film 40 and the polyamic acid 30a of the second film 50 of the exposure portion A1 may be removed by further developing, and the exposed carbon material may be etched. Through the etching process, the film formed of the carbon material is patterned (step S6). The step S6 corresponds to step (E).

[0128] In addition, after step S5, the following process may be performed: similarly to step S4, additional exposure is performed on the exposed portion A2 of the second film 50 through a photomask for the radiation-sensitive resin composition forming the remaining second film 50 (step S7), and further similarly to step S5, development is performed using a developer to form a new exposed portion of the conductive film 70 (step S8). The above steps S7 and S8 correspond to step (F) and step (G), respectively.

[0129] By performing this process, the conductive film 70 can be precisely patterned using the radiation-sensitive resin composition, and at the same time, a conductive film 70 with polyamic acid removed and a pattern formed by changing the structure from polyamic acid to polyimide can be formed. This effect can form finer wiring on a touch screen or a solar cell substrate, for example, and thus can contribute to a more complex wiring design or high integration than before.

[0130] As a coating method of the dispersion, for example, a suitable method such as spray coating, roll coating, spin coating (spin coating), slit die coating (slit coating), rod coating (rod coating), solution dipping, ink jetting, etc. can be used. The conductive film can be formed with a certain thickness by a predetermined method.

[0131] In addition, the radiation-sensitive resin composition can be coated by a suitable method such as spray coating, roll coating, spin coating, slit die coating, bar coating, solution dipping, inkjet, etc. The conductive film can be formed with a certain thickness by a predetermined method.

[0132] Furthermore, the dispersion applied on the organic resin layer 20 preferably has a first polymer content of 1,000 mass % to 100,000 mass % relative to the CNT 30a. When the first polymer content relative to the CNT 30c is within the above range, the solvent inhomogeneity in the drying process can be prevented, and the CNT 30c can be prevented from agglomerating and localizing on the organic resin layer 20 during drying.

[0133] In addition, in order to improve the uniformity of the conductive film 70, it is preferred to perform a process of removing the solvent by a baking process or a solution immersion process for removing the first polymer. In the coating method, from the perspective of uniformity of film thickness and liquid saving of the coating film, a slit die coating method or an inkjet method is preferred. In addition, from the perspective of patterning the electrode only by coating, an inkjet method is more preferred.

[0134] By adopting the above-mentioned method for forming a conductive film, the conductive film formed on the organic resin layer exhibits unique electrical characteristics, has excellent adhesion to the organic resin layer, and has good chemical resistance and flatness.

[0135] In addition, when the conductive film 70 is formed on the organic resin layer 20, the CNTs 30c contained in the first film 40 show high adhesion to the organic resin layer 20, so that the CNTs 30c are not easily localized due to the aggregation of the solvent in the drying process. Furthermore, even in the solution immersion process for removing the first polymer, the CNTs are not peeled off, aggregated, etc., and the localization of the CNTs is suppressed. Even in the case of forming a wiring with a very thin width of the pattern, the effect of not easily generating a portion with a local high resistance or a disconnection can be obtained.

[0136] In order to achieve the above effect, the method for manufacturing the conductive film may include: forming the insulating layer 10 on the substrate 2, forming the organic resin layer 20 after forming the insulating layer 10, and forming the conductive film 70 composed of the CNTs 30a on the organic resin layer 20.

[0137] In addition, the CNT 30a contained in the dispersion preferably contains at least one of single-walled nanotubes or multi-walled nanotubes. By using such a method for manufacturing a conductive film, a semiconductor device having better adhesion between the organic resin layer 20 and the conductive film 70 can be formed. In addition, the manufacturing yield is further improved. In addition, as a carbon material different from the carbon nanotube, for example, graphene or fullerene with excellent conductivity can be used, but as long as it is a material showing conductivity, materials other than these materials can also be used.

[0138] In addition, the method for manufacturing the conductive film can be applied not only to the manufacture of the display panel 1 but also to the manufacture of all electronic devices. Considering that a transparent conductive film can be formed, it is suitable for the manufacture of display panels, touch screens, optical devices, etc.

[0139] In addition, the organic resin layer can also be formed by the following steps. The organic resin layer formed by the following steps shows unique electrical properties, excellent adhesion to CNT, chemical resistance and flatness. In addition, by the above-mentioned formation method, since heating is performed at 140°C or less, thermal degradation of the substrate or the components provided on the substrate can be suppressed. The following is a detailed description of each step.

[0140] [Process (1)]

[0141] In this process, the radiation-sensitive resin composition is used to form a coating film on the insulating layer. Specifically, the radiation-sensitive resin composition is applied to the surface of the insulating layer to form a coating film of the radiation-sensitive resin composition. In addition, in order to remove the solvent contained in the coating film, it is preferred to perform a pre-baking treatment in this process.

[0142] As a coating method for the radioactive composition, for example, a spray method, a roller coating method, a spin coating method (spin coating method), a slit die coating method, a rod coating method, an inkjet method and the like can be used. Among these, as a coating method, an inkjet method is preferred. As the pre-baking conditions, it also varies according to the type of each component, the usage ratio, etc., for example, it can be set at 60°C to 130°C for about 30 seconds to 10 minutes. The film thickness of the formed coating is preferably 0.1μm to 5μm, more preferably 0.1μm to 1μm, and further preferably 0.2μm to 0.4μm, based on the value after pre-baking.

[0143] [Step (2)]

[0144] In this step, a portion of the coating film is irradiated (exposed) with radiation. Specifically, the coating film formed in step (1) is irradiated with radiation through a photomask having a predetermined pattern. Depending on the pattern of the photomask used, a pattern such as contact hole formation or line and space formation can be formed.

[0145] Examples of the radiation used at this time include ultraviolet rays, extreme ultraviolet rays, X-rays, charged particle beams, etc. The photomask used may be a multi-tone mask such as a half-tone mask or a gray-tone mask.

[0146] Examples of ultraviolet rays include g-rays (wavelength 436 nm), i-rays (wavelength 365 nm), and KrF excimer lasers (wavelength 248 nm). Examples of X-rays include synchrotron radiation. Examples of charged particle beams include electron beams. Among these radiations, ultraviolet rays are preferred, and ultraviolet rays having a wavelength of 200 nm or more and 380 nm or less are more preferred. The exposure dose of radiation is preferably 1,000 J / m 2 ~20,000J / m 2 .

[0147] In addition, as appropriate, post exposure bake (PEB) may be performed after the exposure.

[0148] [Step (3)]

[0149] In this step, the coating film irradiated with radiation is developed. Specifically, the coating film irradiated with radiation in step (2) is developed with a developer to remove the irradiated portion. As the developer, for example, an alkaline aqueous solution obtained by dissolving potassium hydroxide, sodium carbonate, triethanolamine, tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide, etc. in water; an organic solvent such as ethanol, isopropyl alcohol, acetone, ethyl acetate, butyl acetate, etc. can be used.

[0150] As a developing method, for example, an appropriate method such as a flooding method, a dipping method, a shaking dipping method, a shower method, etc. can be adopted. The developing time varies depending on the composition of the radiation-sensitive resin composition, but can be set to 30 seconds to 120 seconds, for example.

[0151] [Step (4)]

[0152] In this step, the coating film after the step (3) may be heated. The coating film is hardened by being heated (post-baked) by a heating device such as a hot plate or an oven.

[0153] The upper limit of the heating temperature in this step is 140° C., and the heating temperature may be 130° C., 125° C., or 115° C. According to the above-mentioned formation method, even by heating at a relatively low temperature, the coating film can be formed into a good shape.

[0154] [Verification and evaluation experiment]

[0155] Finally, a verification evaluation experiment was conducted on the dispersibility of CNTs contained in the dispersion applied on the substrate to confirm the extent of the effect obtained by the production method, which will be described below.

[0156] [Synthesis Example 1: Synthesis of polyamic acid]

[0157] 80 g of propylene glycol monomethyl ether acetate (PGMEA) as a polymerization solvent was added to a reaction container, and then a diamine compound and tetracarboxylic dianhydride as a tetracarboxylic acid derivative were added to the polymerization solvent so that the solid content concentration became 20 wt % based on 80 g of the polymerization solvent in total. At this time, in the above example, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (BAHF) was used as a diamine compound, and after dissolving it, 2,3,5-tricarboxycyclopentyl acetic acid dianhydride (TCA) and 1,3-dihydro-1,3-dioxo-5-isobenzofuran carboxylicacid-1,4-phenylene ester (TMHQ) were added as tetracarboxylic dianhydride so that the composition of tetracarboxylic dianhydride was TCA:TMHQ=95:5 (molar ratio). Then, 90 molar parts of tetracarboxylic dianhydride were added based on 100 molar parts of the total amount of the diamine compound. Thereafter, the mixture was reacted at 60° C. for 3 hours. Thus, about 100 g of a polyamic acid solution was obtained. Hereinafter, the solution containing the polyamic acid is referred to as “PAA”.

[0158] [Synthesis Example 2: Synthesis of acrylic acid-based polymer]

[0159] In a flask including a cooling tube and a stirrer, 8 parts by mass of azobisisobutyronitrile and 220 parts by mass of diethylene glycol methyl ether were placed. Then, 15 parts by mass of methacrylic acid, 40 parts by mass of benzyl methacrylate, 10 parts by mass of α-methyl-p-hydroxystyrene, 10 parts by mass of styrene, and 25 parts by mass of n-butyl methacrylate were placed, and after nitrogen substitution, the solution was slowly stirred and the temperature of the solution was raised to 90° C. The temperature was maintained for 5 hours to polymerize, thereby obtaining a solution containing an acrylic polymer. Hereinafter, the solution containing an acrylic polymer is referred to as “PAc”.

[0160] [Comparative Synthesis Example 1: Synthesis of Styrene-Based Polymer Having No Carboxyl Group]

[0161] In a flask including a cooling tube and a stirrer, 8 parts by mass of azobisisobutyronitrile and 220 parts by mass of diethylene glycol methyl ether were placed. Then, 50 parts by mass of styrene and 50 parts by mass of benzyl methacrylate were placed, and after nitrogen substitution, the solution was slowly stirred and the temperature of the solution was raised to 90° C. The temperature was maintained for 5 hours to perform polymerization, thereby obtaining a solution containing a styrene-based polymer having no carboxyl group. Hereinafter, the solution containing a styrene-based polymer having no carboxyl group is referred to as “PSt”.

[0162] [Preparation of CNT-containing dispersion liquid]

[0163] 100,000 parts by mass of N-methyl-2-pyrrolidone (NMP) as a solvent was added to a container containing 10 parts by mass of single-walled carbon nanotubes (SWNT) and 1,000 parts by mass of the polymer (PAA) obtained in Synthesis Example 1 as a first polymer. Then, ultrasonic dispersion was performed for 60 minutes to prepare a dispersion (S-1).

[0164] Next, 100,000 parts by mass of NMP as a solvent was added to a container containing 10 parts by mass of single-walled carbon nanotubes (SWNT) and 1,000 parts by mass of the polymer (PAc) obtained in Synthesis Example 2 as a first polymer, and then ultrasonic dispersion was performed for 60 minutes to prepare a dispersion (S-2).

[0165] Next, 100,000 parts by mass of NMP as a solvent was added to a container containing 10 parts by mass of single-walled carbon nanotubes (SWNT) and 1,000 parts by mass of the polymer (PSt) obtained in Comparative Synthesis Example 1 as a first polymer, and then ultrasonic dispersion was performed for 60 minutes to prepare a dispersion (ss-1).

[0166] [Preparation of Radiation-sensitive Resin Composition (P-1)]

[0167] 30 parts by mass of a quinonediazide compound (condensate of 4,4'-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene]bisphenol and 1,2-naphthoquinonediazide-5-sulfonyl chloride) as a photoacid generator and 3 parts by mass of a bonding aid (1:3-glycidyloxypropyltrimethoxysilane) were mixed with an amount corresponding to 100 parts by mass (solid content) of the polymer (PAA) obtained in Synthesis Example 1, dissolved in a solvent (propylene glycol monomethyl ether acetate (PGMEA)) so as to have a solid content concentration of 30% by mass, and filtered using a membrane filter having a pore size of 0.2 μm to prepare a radiation-sensitive resin composition (P-1).

[0168] [Preparation of Radiation-sensitive Resin Composition (P-2)]

[0169] 30 parts by mass of a quinonediazide compound (condensate of 4,4'-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene]bisphenol and 1,2-naphthoquinonediazide-5-sulfonyl chloride) as a photoacid generator and 3 parts by mass of a bonding aid (1:3-glycidyloxypropyltrimethoxysilane) were mixed with an amount corresponding to 100 parts by mass (solid content) of the polymer (PAc) obtained in Synthesis Example 2, dissolved in a solvent (propylene glycol monomethyl ether acetate (PGMEA)) so as to have a solid content concentration of 30% by mass, and filtered using a membrane filter having a pore size of 0.2 μm to prepare a radiation-sensitive resin composition (P-2).

[0170] [Preparation of Radiation-sensitive Resin Composition (P-3)]

[0171] 30 parts by mass of a quinonediazide compound (condensate of 4,4′-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene]bisphenol and 1,2-naphthoquinonediazide-5-sulfonyl chloride) as a photoacid generator, 10 parts by mass of lactam black (Irgaphor Black S 0100CF manufactured by BASF) as a colorant, and 3 parts by mass of an adhesion aid (1:3-glycidyloxypropyltrimethoxysilane) were mixed with an amount corresponding to 100 parts by mass (solid content) of the polymer (PAA) obtained in Synthesis Example 1, and a solvent (propylene glycol monomethyl ether acetate (PGMEA)) was added so as to have a solid content concentration of 30% to prepare a radiation-sensitive resin composition (P-3).

[0172] [Preparation of radiation sensitive resin composition (pp-1)]

[0173] 30 parts by mass of a quinonediazide compound (condensate of 4,4'-[1-[4-[1-(4-hydroxyphenyl)-1-methylethyl]phenyl]ethylidene]bisphenol and 1,2-naphthoquinonediazide-5-sulfonyl chloride) as a photoacid generator and 3 parts by mass of a bonding aid (1:3-glycidyloxypropyltrimethoxysilane) were mixed with an amount corresponding to 100 parts by mass (solid content) of the polymer (PSt) obtained in Comparative Synthesis Example 1, dissolved in a solvent (propylene glycol monomethyl ether acetate (PGMEA)) so as to have a solid content concentration of 30% by mass, and filtered using a membrane filter having a pore size of 0.2 μm to prepare a radiation-sensitive resin composition (pp-1).

[0174] [Evaluation of CNT-containing dispersion liquid]

[0175] (1) Evaluation of CNT dispersion

[0176] The dispersion (S-1), dispersion (S-2), and dispersion (ss-1) were placed in a flat place at 25°C. Regarding the evaluation, if the initial dispersion state is maintained after 1 week and the CNT does not settle, it is set as "the best (A)", if the initial dispersion state is maintained until 3 days later and the CNT does not settle, it is set as "excellent (B)", if the initial dispersion state is maintained until 1 day later and the CNT does not settle, it is set as "good (C)", if the initial dispersion state is maintained until 3 hours later and the CNT does not settle, it is set as "acceptable (D)", and if the sedimentation or aggregation of CNT is observed within 3 hours, it is set as "poor (E)". The results are shown in Table 1.

[0177] (2) Evaluation of CNT dispersion stability (durability)

[0178] Prepare a dispersion in the same manner as described in (1). Place the obtained dispersion in a flat place at 40°C and observe the dispersion state over time. Regarding the evaluation, if the initial dispersion state is maintained after 1 week and the CNT does not settle, it is set as "the best (A)", if the initial dispersion state is maintained until 3 days later and the CNT does not settle, it is set as "excellent (B)", if the initial dispersion state is maintained until 1 day later and the CNT does not settle, it is set as "good (C)", if the initial dispersion state is maintained until 3 hours later and the CNT does not settle, it is set as "acceptable (D)", and if sedimentation or aggregation is observed after 3 hours, it is set as "poor (E)". The results are shown in Table 1.

[0179] (3) Evaluation of coating properties of dispersion

[0180] The obtained dispersion (S-1), dispersion (S-2), and dispersion (ss-1) were applied to a glass substrate formed with an organic resin layer by spin coating, and dried on a hot plate at 80°C for 10 minutes, thereby forming a coating film with a film thickness of 0.1 μm in the center of the substrate. The coating film was observed under a microscope with a magnification of 50 times to check whether there were uneven film thickness and pinholes in the coating film. Regarding the evaluation, the case where neither uneven film thickness nor pinholes were observed was set as the "best (A)" for coating, and the case where at least one of uneven film thickness and pinholes was slightly observed was set as the "good (B)" for coating. The case where at least one of uneven film thickness and pinholes was clearly observed was set as the "poor (C)" for coating. The results are shown in Table 1.

[0181] [Evaluation of Radiation-sensitive Resin Composition]

[0182] The substrates on which the coating films were formed were respectively referred to as (S-1) substrate, (S-2) substrate, and (ss-1) substrate.

[0183] (4) Evaluation of coating properties of radiation sensitive resin composition

[0184] By spin coating, the radiation-sensitive resin composition (P-1), the radiation-sensitive resin composition (P-2), the radiation-sensitive resin composition (P-3), and the radiation-sensitive resin composition (pp-1) were applied to the (S-1) substrate, the (S-2) substrate, and the (ss-1) substrate, and dried on a hot plate at 90°C for 2 minutes to form a coating film with a thickness of 4 μm. The coating film was observed under a microscope with a magnification of 50 times to check whether there were uneven film thickness and pinholes in the coating film. Regarding the evaluation, the case where neither uneven film thickness nor pinholes were observed was set as the "best (A)" for coating, and the case where at least one of uneven film thickness and pinholes was slightly observed was set as the "good (B)" for coating. The case where at least one of uneven film thickness and pinholes was clearly observed was set as the "poor (C)" for coating. The results are shown in Table 2.

[0185] (5) Evaluation of pattern shape

[0186] An exposure machine (Canon MPA-600FA (ghi ray hybrid)) was used with a photomask having a line and space pattern of 10 μm at 500 mJ / cm 2 The substrates each having a radiation-sensitive resin composition coating film formed thereon were exposed to light at an exposure amount of , and then developed using a 2.38 mass % tetramethylammonium hydroxide aqueous solution at 23° C. by a flooding method for 80 seconds. Subsequently, the substrates were washed with ultrapure water for 1 minute and then dried to form a 10 μm line and space pattern.

[0187] Thereafter, the obtained pattern shape is evaluated using a scanning electron microscope (SEM). If the cross section of the obtained pattern is a positive cone shape, it is evaluated as "good (A)", and the case where the cone angle is smaller than the positive cone and is nearly perpendicular to the substrate is evaluated as "acceptable (B)", and the case where there is a dissolved residue in the space part and the development is considered insufficient is evaluated as "bad (C)". When applied to the embankment material of an organic EL, the film formation of the luminescent material with a positive cone cross section of the pattern becomes smooth, and a part of the thin film layer will not become thinner or interrupted, which is preferred in terms of preventing the uneven brightness in the luminescent area. The results are shown in Table 2.

[0188] (6) Evaluation of CNT removal performance

[0189] When the radiation-sensitive resin composition coating film is removed by development of the obtained pattern-formed substrate, the underlying CNT conductive layer can be confirmed in the space portion of the line-and-space pattern.

[0190] Figure 7 and Figure 8 All of them are photos of the surface of the spatial distribution of the substrate taken using an atomic force scanning microscope (Atomic Force Microscope (AFM)). Figure 7 This is an example of a photograph of a substrate surface where the unevenness of CNTs can be observed. Figure 8 This is an example of a photograph of a substrate surface where no unevenness of CNTs is observed using AFM, that is, CNTs are covered with a resin or a first polymer. Figure 7 The samples with visible CNT (carbon nanotube) exposure as shown in the figure were rated as "good (A)", and the samples with visible CNT (carbon nanotube) exposure as shown in the figure were rated as "good (A)". Figure 8 Those in which part of the CNT was exposed as shown were rated as "OK (B)", and those in which the surface was covered with resin and the CNT was not visible, or those in which the CNT could not be identified due to poor film formation were rated as "NO (C)".

[0191] (7) Criteria for determination

[0192] In the evaluations related to the dispersion and the evaluations of the radiation-sensitive resin composition for the substrate, at least one sample showing "bad" result was judged as NG.

[0193] The above results are summarized in Tables 1 and 2 below.

[0194] [Table 1]

[0195] Dispersion Dispersants CNT dispersion CNT dispersion stability Coating properties of dispersion determination S-1 PAA A A A OK S-1 PAA A A A OK S-2 PAc B C B OK S-2 PAc B C B OK ss-1 Psf C D C NG

[0196] [Table 2]

[0197]

[0198] Description of Figure Numbers

[0199] 1: Display panel

[0200] 2: Base material

[0201] 10: Insulation layer

[0202] 20: Organic resin layer

[0203] 30: Coating film

[0204] 40: First Film

[0205] 50: Second Film

[0206] 60: Photomask

[0207] 70: Conductive layer

[0208] 80: Pattern

Claims

1. A method for manufacturing a conductive film, comprising: Step (A), coating a dispersion liquid containing a first polymer having any one of a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group and a carbon material on a main surface of a substrate and drying the dispersion liquid to form a first film; Step (B), coating the first film with a radiation-sensitive resin composition containing a second polymer having any one of a carboxyl group, a hydroxyl group, and a phenolic hydroxyl group and a photoacid generator to form a second film; Step (C), exposing a portion of the second film; as well as A step (D) of removing the first polymer and the second polymer in the portion exposed in the step (C) after the step (C) is performed.

2. The method for producing a conductive film according to claim 1, wherein: The step (A) applies the first polymer having a polyamic acid structure, and the step (B) applies the second polymer having a polyamic acid structure.

3. The method for producing a conductive film according to claim 2, wherein: The step (A) is to apply the dispersion containing the first polymer having a polyamic acid structure and an organic solvent.

4. The method for producing a conductive film according to claim 1, wherein: The step (B) is to apply the radiation-sensitive resin composition containing the second polymer having a polyamic acid having a structural unit represented by the following general formula (1) as a main component. [Chemistry 1] (In formula (1), R 1 is a tetravalent organic group constituting a tetracarboxylic acid, R 2 is a divalent organic group constituting a diamine, and n represents a positive integer. ) 5. The method for producing a conductive film according to claim 1, wherein: The step (A) comprises applying the dispersion containing at least one carbon material selected from the group consisting of carbon nanotubes, graphene, and fullerene.

6. The method for manufacturing a conductive film according to claim 1, wherein: The step (B) is to apply the radiation-sensitive resin composition containing a quinonediazide compound as the photoacid generator.

7. The method for manufacturing a conductive film according to claim 1, wherein: The step (B) is to apply the radiation-sensitive resin composition containing a colorant.

8. The method for manufacturing a conductive film according to claim 1, wherein: The step (A) includes applying the dispersion liquid containing the first polymer in an amount ranging from 1,000% by mass to 10,0000% by mass based on the content of the carbon material.

9. The method for manufacturing a conductive film according to claim 1, wherein: In the step (A), the dispersion is applied by any coating method selected from the group consisting of spin coating, slit coating, bar coating, spray coating, and inkjet coating.

10. The method for manufacturing a conductive film according to claim 1, wherein: In the step (B), the radiation sensitive resin composition is applied by any coating method selected from the group consisting of spin coating, slit coating, bar coating, spray coating, and ink jet coating.

11. The method for manufacturing a conductive film according to claim 1, wherein: In the step (C), exposure is performed through a half-tone mask.

12. The method for manufacturing a conductive film according to claim 2, wherein: In the step (D), an alkaline aqueous solution, an organic solvent, or a mixed solution thereof is used as a developer to remove the first polymer and the second polymer. 13 . A dispersion liquid used in the method for producing a conductive film according to claim 1 . 14 . A radiation-sensitive resin composition used in the method for producing a conductive film according to claim 1 . 15 . A light-emitting element comprising a conductive film manufactured by the method for manufacturing a conductive film according to claim 1 .

Citation Information

Patent Citations

  • Method of manufacturing base material including transparent conductive film

    JP2010214837A